Diversity of bacteria associated with corn roots inoculated with Canadian woodland soils, and description of Pseudomonas aylmerense sp. nov. Issue 8 (August 2018) - Tchagang, Caetanie F.; Xu, Renlin; Overy, David; Blackwell, Barbara; Chabot, Denise; Hubbard, Keith; Doumbou, Cyr Lézin; Bromfield, Eden S.P.; Tambong, James T.
Abstract: Bacteria associated with corn roots inoculated with soils collected from the Canadian woodlands were isolated and characterized. Genus-level identification based on 16S rRNA sequence analysis classified the 161 isolates in 19 genera. The majority (64%) of the isolates were affiliated with the genus Pseudomonas . Further analysis of the Pseudomonas isolates based on BLASTn and rpo D- rpo B- gyr B concatenated gene phylogeny revealed three unique clusters that could not be assigned to known species. This study reports the taxonomic description of one of the distinct lineages represented by two strains (S1E40 T and S1E44) with P. lurida LMG 21995 T, P. costantinii LMG 22119 T, P. palleroniana LMG 23076 T, P. simiae CCUG 50988 T and P. extremorientalis LMG 19695 T as the closest taxa. Both strains showed low ANIm (<90%) and genome-based DNA-DNA hybridization (<50%) values, which unequivocally delineated the new strains from the closest relatives. These findings were supported by multilocus sequence analysis (MLSA) and DNA fingerprinting. In addition, growth characteristics and biochemical tests revealed patterns that differed from the related species. Strains S1E40 T and S1E44 are Gram-negative, aerobic, rod-shaped and motile by at least one flagellum; and grew optimally at 30 °C. The predominant polar lipid is phosphatidylethanolamine while the major respiratory quinone is ubiquinone-9. Based on phenotypic and genotypic data presented here, strains S1E40 T and S1E44 represent a novel species for which the name Pseudomonas aylmerense sp . nov. is proposed. The type strain is S1E40 T (= LMG 30784 T = DOAB 703 T = HAMI 3696 T ) with a G + C content of 61.6%.